The Relationship between Family Support and Anxiety Level in Preoperative Major Elective General Anesthesia Patients at dr. Soedomo Hospital Trenggalek - Ridho, Syeikhu Alfa; Widodo, Dyah; Sulastyawati, Sulastyawati; Ciptaningtyas, Maria Diah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
surgical process. Family support plays a crucial role in helping patients manage preoperative anxiety. The study aimed to analyze the relationship between family support and anxiety levels in patients undergoing major elective surgery with general anesthesia. The research design was cross-sectional. The study population consisted of 92 patients, with a sample size of 75 recruited through non-probability purposive sampling. The study utilized family support and Amsterdam preoperative anxiety and information Scale (APAIS) questionnaires as instruments. Data were analyzed using descriptive and inferential statistical tests, including Spearman’s rank correlation (Rho) with a p-value less than 0.05 was considered statistically significant. The results showed that almost all participant received high levels of family support (81.3%) and moderate level of preoperative anxiety (81.3%). The Spearman rank test indicated a significant relationship between family support and anxiety levels (p-value = 0.000 0.05) with a very strong, negative correlation (r = -.870). In conclusion, higher the family support is associated with lower anxiety level in preoperative patients. It is recommended that families provide consistent support during preoperative phase to help reduce patient level of anxiety.